Exchange rate pass-through to domestic prices in the European transition economies - Rajmund Mirdala (Institut für Ost- und Südosteuropaforschung (IOS), 2016)
Vulnerability of exchange rates to the external price shocks as well as their absorption capabilities represents one of the most discussed area in the fixed versus flexible exchange rate dilemma. Ability of exchange rates to serve as a traditional vehicle for a transmission of external shocks to domestic prices is affected by exchange rate arrangement adopted by monetary authorities. As a result, exchange rate volatility determines the overall dynamics of pass-through effects and associated absorption capability of exchange rate. Ability of exchange rates to transmit external (price) shocks to the national economy represents one of the most discussed areas relating to the current stage of the monetary integration in the European single market. The problem is even more crucial when examining crisis related redistributive effects. In the paper we analyze exchange rate pass-through to domestic prices in the European transition economies. We estimate VAR model to investigate (1) responsiveness of exchange rate to the exogenous price shock to examine the dynamics (volatility) in the exchange rate leading path followed by the unexpected oil price shock and (2) effect of the unexpected exchange rate shift to domestic price indexes to examine its distribution along the internal pricing chain. Our results indicate that there are different patterns of exchange rate passthrough to domestic prices according to the baseline period as well as the exchange rate regime diversity.
urn:nbn:de:101:1-201611293156
Keywords: C32; E31; F41; 330; exchange rate pass-through; inflation; VAR; Cholesky decomposition; impulse-response function